A novel thermostable and halophilic thioredoxin reductase from the Red Sea Atlantis II hot brine pool - Badiea, Elham A. (PLoS One, 2019)
The highly extreme conditions of the lower convective layer in the Atlantis II (ATII) Deep brine pool of the Red Sea make it an ideal environment for the search for novel enzymes that can function under extreme conditions. In the current study, we isolated a novel sequence of a thioredoxin reductase (TrxR) enzyme from the metagenomic dataset established from the microbial community that resides in the lower convective layer of Atlantis II. The gene was cloned, expressed and characterized for redox activity, halophilicity, and thermal stability. The isolated thioredoxin reductase (ATII-TrxR) was found to belong to the high-molecular-weight class of thioredoxin reductases. A search for conserved domains revealed the presence of an extra domain (Crp) in the enzyme sequence. Characterization studies of ATII-TrxR revealed that the enzyme was halophilic (maintained activity at 4 M NaCl), thermophilic (optimum temperature was 65°C) and thermostable (60% of its activity was retained at 70°C). Additionally, the enzyme utilized NADH in addition to NADPH as an electron donor. In conclusion, a novel thermostable and halophilic thioredoxin reductase has been isolated with a unique sequence that adapts to the harsh conditions of the brine pools making this protein a good candidate for biological research and industrial applications.